Laboratory characterization of an aerosol chemical speciation monitor with PM2.5 measurement capability. Issue 1 (2nd January 2017) - Xu, Wen; Croteau, Philip; Williams, Leah; Canagaratna, Manjula; Onasch, Timothy; Cross, Eben; Zhang, Xuan; Robinson, Wade; Worsnop, Douglas; Jayne, John
ABSTRACT: The Aerodyne Aerosol Chemical Speciation Monitor (ACSM) is well suited for measuring non-refractory particulate matter up to approximately 1.0 µm in aerodynamic diameter (NR-sub-PM1 ). However, for larger particles the detection efficiency is limited by losses in the sampling inlet system and through the standard aerodynamic focusing lens. In addition, larger particles have reduced collection efficiency due to particle bounce at the vaporizer. These factors have limited the NR-sub-PM1 ACSM from meeting PM2.5 (particulate matter with aerodynamic diameter smaller than 2.5 µm) monitoring standards. To overcome these limitations, we have redesigned the sampling inlet, the aerodynamic lens, and particle vaporizer. Both the new lens and vaporizer are tested in the lab using a quadruple aerosol mass spectrometer (QAMS) system equipped with light scattering module. Our results show that the capture vaporizer introduces additional thermal decomposition of both inorganic and organic compounds, requiring modifications to the standard AMS fragmentation table, which is used to partition ion fragments to chemical classes. Experiments with mixed NH4 NO3 and (NH4 )2 SO4 particles demonstrated linearity in the NH4 + ion balance, suggesting that there is no apparent matrix effect in the thermal vaporization-electron impact ionization detection scheme for mixed inorganic particles. Considering a typical ambient PM2.5 size distribution, we found that 89% of the non-refractory mass is detected with the new system, while only 65% with the old system. The NR-PM2.5 system described here can be adapted to existing Aerodyne Aerosol Mass Spectrometer (AMS) and ACSM systems. Copyright © 2017 American Association for Aerosol Research